What do we need to know and understand about p53 to improve its clinical value?. Issue 4 (6th May 2021) - Salomao, Norman; Karakostis, Konstantinos; Hupp, Ted; Vollrath, Friz; Vojtesek, Borivoj; Fahraeus, Robin
Abstract: Few proteins are more studied than the p53 tumour suppressor, but what have we learned from these studies and what do we really know about p53 that can benefit clinical practice? The DNA sequence encoding p53 is frequently mutated in cancers but the functional outcomes of single mutations, in respect to loss or gain of different activities, especially in relation to immune evasion, are not clear. This illustrates p53's complexity which even after 40 years keeps providing surprises, but also explains why it has not yet lived up to its potential to benefit cancer treatment. We have reassessed a few key experiments that shaped the p53 field and we take a closer look at the interpretations of these experiments: what they have taught us, the resulting dogmas, and their potential clinical importance. One outcome is a more dynamic view of p53 in terms of its activity, its regulation, and downstream effectors, which will benefit the clinical application of p53 for diagnosis, prognosis, and therapy. Mutations and regulatory factors can have different effects on p53 activity depending on context, important but neglected aspects when interpreting p53 and its pathways in cancers. Even though p53 is undoubtedly unique as a multifunctional hub in different cellular pathways, the concept of a factor taking up different functions within a regulatory pathway during different conditions is not. In this sense, p53 continues to lead the way for a better understanding of the cellular and molecular mechanisms underlying cancer development in vivo . © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.